Economics of nuclear power plant investment: Monte Carlo simulations of generation III/III+ investment projects - Ben Wealer; Simon Bauer; Leonard Göke; Christian R. von Hirschhausen; Claudia Kemfert (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper analyzes nuclear power plant investments using Monte Carlo simulations of economic indicators such as net present value (NPV) and levelized cost of electricity (LCOE). In times of liberalized electricity markets, largescale decarbonization and climate change considerations, this topic is gaining momentum and requires fundamental analysis of cost drivers. We adopt the private investors' perspective and ask: What are the investors' economics of nuclear power, or - stated differently - would a private investor consider nuclear power as an investment option in the context of a competitive power market? By focusing on the perspective of an investor, we leave aside the public policy perspective, such as externalities, cost-benefit analysis, proliferation issues, etc. Instead, we apply a conventional economic perspective, such as proposed by Rothwell (2016) to calculate NPV and LCOE. We base our analysis on a stochastic Monte Carlo simulation to nuclear power plant investments of generation III/III+, i.e. available technologies with some experience and an extensive scrutiny of cost data. We define and estimate the main drivers of our model, i.e. overnight construction costs, wholesale electricity prices, and weighted average cost of capital, and discuss reasonable ranges and distributions of those parameters. We apply the model to recent and ongoing investment projects in the Western world, i.e. Europe and the United States; cases in non-market economies such as China and Russia, and other non-established technologies (Generation IV reactors and small modular reactors) are excluded from the analysis due to data issues. Model runs suggest that investing in nuclear power plants is not profitable, i.e. expected net present values are highly negative, mainly driven by high construction costs, including capital costs, and uncertain and low revenues. Even extending reactor lifetimes from currently 40 years to 60 years does not improve the results significantly. We conclude that the economics of nuclear power plants are not favorable to future investments, even though additional costs (decommissioning, long-term storage) and the social costs of accidents are not even considered.
Keywords: Q40; D24; G00; 330; nuclear power; nuclear financing; investment; levelized cost of electricity; monte carlo simulation; uncertainty